Neuropsychiatric Drugs Against COVID-19: What is the Clinical Evidence? - Mueller, Juliane K.; Riederer, Peter; Müller, Walter E. (Pharmacopsychiatry, 2022)
Since the beginning of the coronavirus disease (COVID)-19 pandemic, the need for effective treatments for COVID-19 led to the idea of “repurposing” drugs for antiviral treatment. Several antipsychotics and antidepressants have been tested for in vitro activity against the severe acute respiratory syndrome coronavirus 2. Chlorpromazine, other phenothiazine antipsychotics, and the antidepressant fluoxetine were found to be rather potent in these studies. However, whether effective plasma concentrations can be obtained with clinically accepted doses of these drugs is not clear. Data of COVID-19 patients are not yet available but several clinical studies are currently underway.The specific serotonin reuptake inhibitor fluvoxamine is a potent Sigma-1 receptor agonist and reduces inflammation in animal models of cytokine-stress. Accordingly, fluvoxamine treatment was superior to placebo in reducing impaired respiratory function and other symptoms of inflammation in COVID-19 patients in a placebo-controlled clinical study and another open clinical trial. The beneficial effects of fluvoxamine on the course of COVID-19 were recently confirmed in a large placebo-controlled double-blind trial with several hundred patients.Inflammation represents a major risk factor for many psychiatric disorders which explains the high susceptibilitiy of COVID-19 patients for psychiatric diseases. Many antidepressants and antipsychotics possess anti-inflammatory properties independent of sigma-1 activity which might be important to reduce psychiatric symptoms of COVID-19 patients and to improve respiratory dysfunction and other consequences of inflammation. This might explain the rather unspecific benefit which has been reported for several cohorts of COVID-19 patients treated with different psychotropic drugs.
Keywords: COVID-19; antipsychotics; antidepressant drugs; anti-viral and anti-inflammatory effects